Distance Entrepreneurship Entrepreneurship Learning and Innovation Culture In Kingdom of Saudi Arabia - Bata, Ismail; Alharkan, Ibrahim; Alenazi, Sultan (The Arab Journal of Administration, 2021)
The aim of this study is to demonstrate the basic components of education, that Saudi universities can adopt as an introduction to the educational process. Analysis of the elements and obstacles of creativity, among students and the importance of teamwork in motivating, this as well as building a positive perception about e-learning programs in Saudi universities. The problem of the study was to search for the possibility of working, a remote e-program to achieve creativity and innovation in Saudi society and researchers followed the descriptive approach to describe the study community and determine, its features In terms of numbers, gender and interaction in the program, the number of graduates and the preparation of the graduated work plans of the program and the geographical areas of the participants and the participating parties. The data collected through the study tool (questionnaire) to test and analyze the logical assumptions, about the aspects of the program to reach conclusions on the assumptions of elements of creativity, innovation and interactive environment, within the program and the program’s ability to prepare students to prepare business plans for the pilot projects they propose and develop among themselves and their impact on the community. The researchers reached important results: the positive impact of the students and have a passion for creativity and dissemination of entrepreneurship culture, the program stimulated the 738 students, of whom 239 graduated, and formed creative groups whose members did not participate previously through the program (112) groups. Each group aims to prepare an action plan for the pilot project they agree on. (16) additional participants from outside the program. The study recommended the need to find a program of incubation and funding for projects resulting from the program Efforts between creative ideas and turn them into real projects, that serve the community and contribute to the Saudi Vision 2030.